Ovarian dynamics and fecundity regulation in blueback herring, Alosa aestivalis, from the Connecticut River, US. (4th November 2020) - Mouchlianitis, Foivos A.; Schultz, Eric T.; dos Santos Schmidt, Thassya C.; Davis, Justin P.; Ganias, Kostas
Abstract: We analyzed ovarian dynamics of anadromous blueback herring, Alosa aestivalis, in Connecticut River with the principal aim of exploring oocyte recruitment and how it shapes the fecundity pattern. We examined the oocyte release strategy and analyzed spawning cyclicity by linking oocyte growth to the degeneration of postovulatory follicles. Females were accordingly classified as pre‐spawners, early and late active spawners, and oocyte recruitment intensity was compared among the different spawning phases. Oocyte recruitment occurred continuously and in parallel with spawning activity, a pattern which is diagnostic of indeterminate fecundity. However, both fecundity and oocyte recruitment intensity progressively decreased (tapered) throughout spawning, until the ovary was depleted of vitellogenic oocytes. There was no massive atresia of vitellogenic oocytes at the end of the spawning season, which is atypical of indeterminate spawners. We propose that tapering in oocyte recruitment and fecundity is an adaptation to the high energetic expenditure of the upstream spawning migration.